2003
DOI: 10.1029/2002gl016730
|View full text |Cite
|
Sign up to set email alerts
|

Current sheet structure near magnetic X‐line observed by Cluster

Abstract: [1] During the interval 0947 -0951 UT on 1 October 2001, when Cluster was located at X GSM = À16.4 R E near Z GSM = 0 in the pre-midnight magnetotail, the Cluster barycenter crosses the neutral sheet four times. High speed proton flow, with reversal from tailward to Earthward, was detected during the crossings. Using a linear gradient/curl estimator technique we estimate current density and magnetic field curvature within the crossings. These observations exhibit the tailward passage of an X-line over the Clus… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

24
265
1
1

Year Published

2004
2004
2015
2015

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 256 publications
(291 citation statements)
references
References 19 publications
24
265
1
1
Order By: Relevance
“…Usually the perpendicular velocity moment is interpreted as convecting plasma flows across the magnetic field in the E Â B direction. For example, Runov et al [2003] interpreted the October 1, 2001 event as a passage of a reconnection neutral line from Earthward to tailward of the spacecraft using the magnetic fields and velocity moments. However, this study suggests that the large velocity moments in some instances come from the highly non-gyrotropic distributions that result from remote sensing of a stationary Maxwellian distribution.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Usually the perpendicular velocity moment is interpreted as convecting plasma flows across the magnetic field in the E Â B direction. For example, Runov et al [2003] interpreted the October 1, 2001 event as a passage of a reconnection neutral line from Earthward to tailward of the spacecraft using the magnetic fields and velocity moments. However, this study suggests that the large velocity moments in some instances come from the highly non-gyrotropic distributions that result from remote sensing of a stationary Maxwellian distribution.…”
Section: Discussionmentioning
confidence: 99%
“…[4] Cluster observations of the near-Earth magnetotail demonstrate the formation of thin current sheets with a thickness of an ion Larmor radius scale during active periods [Shen et al, 2003;Runov et al, 2003] Marcucci et al [2004] reports on energetic O+ ions emerging from the dayside magnetopause, which form highly anisotropic distributions in the magnetosheath. This study presents the results of a test particle simulation that show that the highly non-gyrotropic distributions can come from remote sensing of a thin current sheet.…”
Section: Introductionmentioning
confidence: 99%
“…If a spacecraft flies through the ion diffusion region along the outflow direction, the expected large-scale signatures would be a reversal of plasma jetting, accompanied by a reversal of the normal component of the magnetic field. Coinciding with these reversals, one would also expect to detect portions of the quadrupolar out-of-plane Hall magnetic field (e.g., Oieroset et al 2001;Runov et al 2003;Borg et al 2005;Eastwood et al 2010aEastwood et al , 2010b) and bi-polar Hall electric field (Wygant et al 2005;Borg et al 2005;. Figure 1 displays an example of reported ion diffusion crossing by the Cluster spacecraft (Borg et al 2005) indicated by the reversals of the reconnection jets ( Fig.…”
Section: Magnetotailmentioning
confidence: 99%
“…While technically it is possible for a spacecraft to encounter the diffusion region from any direction, a majority of the diffusion region encounters reported in the Near-Earth magnetotail have been associated with the tailward motion of an X-line past the spacecraft (e.g., Runov et al 2003;Borg et al 2005;Chen et al 2008a;Eastwood et al 2010aEastwood et al , 2010b, i.e. the spacecraft crossed the diffusion region along the outflow direction, observing both exhausts.…”
Section: Magnetotailmentioning
confidence: 99%
“…Later, He et al (2008b) reconstructed the magnetic field around the same null and inferred that it was moving earthward. Xiao et al (2007) discussed the same event in terms of a pair of spiral nulls of opposite polarity (also see, Runov et al 2003;Cattell et al 2005;Wygant et al 2005). Based on the orientation of the spines and fans of the null points, Xiao et al (2007) concluded that the nulls were connected by a separator.…”
Section: Plasma Phenomena As Measured In Three Dimensionsmentioning
confidence: 99%